Konsep Produksi dalam Pemikiran Ibn Khaldūn: Analisis Teoretis dan Relevansinya bagi Ekonomi Islam Kontemporer: The Concept of Production in Ibn Khaldūn's Thought: Theoretical Analysis and Its Relevance for Contemporary Islamic Economics - Azwar Azwar; Muslimin H. Kara; Askar Patahuddin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to describe the concept of production in Ibn Khaldūn’s thought, analyze its philosophical, normative, and historical foundations, and evaluate its relevance to the development of contemporary Islamic economics, particularly the halal industry. The study employs a qualitative-descriptive approach based on library research, using content analysis of Ibn Khaldūn’s Muqaddimah and related literature to examine the concept of production within the context of the modern economy. The findings indicate that, in Ibn Khaldūn’s perspective, production is an integral part of civilization (‘umrān) and is not merely understood as a technical process, but also as a social activity involving human labor, division of labor, social solidarity (‘asabiyyah), and institutional strengthening. His concept of production is rooted in Sharīʿah values such as justice and maṣlaḥah, and is shaped by historical and political experiences that form a comprehensive view of the relationship between state stability, productive capacity, and societal welfare. Furthermore, the study highlights that Ibn Khaldūn’s thought remains highly relevant to contemporary Islamic economics. Its principles can serve as a foundation for strengthening the halal industry through improving human capital quality, institutional governance, halal certification, access to Islamic finance, and equitable fiscal policies. Therefore, Ibn Khaldūn’s concept of production offers a rich and applicable analytical framework for sustainable Islamic economic development. The implication is that this framework can be used as a conceptual basis for formulating policies and strategies for sustainable and socially oriented halal industry development.